2016
DOI: 10.18632/oncotarget.13225
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating concordance between blood-based and patient-matched tumor molecular testing within pancreatic cancer patients participating in the Know Your Tumor (KYT) initiative

Abstract: Recent improvements in next-generation sequencing (NGS) technology have enabled detection of biomarkers in cell-free DNA in blood and may ultimately replace invasive tissue biopsies. However, a better understanding of the performance of blood-based NGS assays is needed prior to routine clinical use. As part of an IRB-approved molecular profiling registry trial of pancreatic ductal adenocarcinoma (PDA) patients, we facilitated blood-based NGS testing of 34 patients from multiple community-based and high-volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…None of the KRAS mutations from the seven patients with KRAS mutant primary tumors were detected in the ccfDNA at the time of diagnosis, while mutations in other genes were detected. Mutant KRAS ccfDNA was, however, found by others in 10 of 34 pancreatic patients (29%) [22] or in 136 of 188 (72.3%) of patients with metastatic PDAC [23]. Another study showed that mutant KRAS ccfDNA was detected in 14.8%, 45.5%, 30.8%, and 57.9% of age-matched controls, localized, locally advanced, and metastatic PDAC patients, respectively [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the KRAS mutations from the seven patients with KRAS mutant primary tumors were detected in the ccfDNA at the time of diagnosis, while mutations in other genes were detected. Mutant KRAS ccfDNA was, however, found by others in 10 of 34 pancreatic patients (29%) [22] or in 136 of 188 (72.3%) of patients with metastatic PDAC [23]. Another study showed that mutant KRAS ccfDNA was detected in 14.8%, 45.5%, 30.8%, and 57.9% of age-matched controls, localized, locally advanced, and metastatic PDAC patients, respectively [20].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed detection of EGFR T790M mutant DNA in the circulation of cancer patients was improved by selecting for shorter DNA fragment lengths [26]. Comparisons of tumor tissue somatic DNA and ccfDNA mutation rate can be impacted by the application of different sequencing technologies and amplicon sizes [27, 28] as well as read depths and these technical issues may bias the data interpretation [22]. To avoid this pitfall we used a platform that is adapted to the detection of short DNA fragments found as circulating cell-free DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Discordance observed between cfDNA and tumour tissue may be due to the subclonal presentation of drivers in the tumour in later stages of the disease, which can affect the detectability of these drivers in cfDNA and impact concordance rates [86]. A multitude of studies across the field of solid tumours (i.e., prostate, NSCLC, breast, neuroblastoma, renal, gastrointestinal, pancreatic, thyroid and melanoma) focus on individual ( Table 2) or multiple malignancies (Table 3) and report a trend for high agreement between cfDNA and tumour tissue with respect to actionable driver alterations, but with notable exceptions [70,[89][90][91][92][93][94]. In Tables 2 and 3, we have included studies that compare the extent to which cfDNA reflects driver and actionable driver alterations of the primary or metastatic tumours.…”
Section: Gene Type and The Effect Of Drug Therapymentioning
confidence: 99%
“…In pancreatic cancer, high ctDNA levels of KRAS and/or other mutations have been associated with poor progression-free survival (PFS) and/or OS [47,48]. However, low concordance between the blood and tissue samples has been reported in patients with pancreatic ductal adenocarcinoma [49].…”
Section: Pancreatic and Biliary Tract Carcinomasmentioning
confidence: 99%